SINGLE-O-SHELTER HUNA (Cherax albertisi) AND REDCLAW (C. quadricarinatus) CULTURE - Taufik Ahmad; Lilis Sofiarsih; Nuryadi Nuryadi; G. Apriyana (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2007)
Many hatcheries successfully produced and sold cherax as ornamental crayfish. The attempt to culture cherax in earthen pond to produce consumable size yabbies facing the fact that cherax is a good hole digger and usually escapes through the hole in dyke. Single-o-shelter meant to provide shelter for every single spawner as well as hideout for the juvenile produced. The shelter for spawner was a 25 inches long and 2.0 inches diameter PVC pipe randomly spread on pond bottom. Aquatic weed (Vallisneria torta) grew in the shallow part of pond to provide hiding place for juvenile. The species stocked is huna and redclaw, each at density of 2 and 6 sets of spawner. One set of spawner consists of 3 males and 5 females weighing averagely around 20 g each. The experimental units are randomly selected to facilitate random block design in 2 rearing period as replicate. The pond dimension is 10x10 m, divide into 3 compartments i.e. feeding, ground, nursery ground and harvest ditch. Water depth at nursery ground was 30 cm and at the other compartments at 60 cm. Follow gravity force, the water in ponds flows at 50—100 L minute-1. Self-made diet distributed into pond twice a day to meet 3% daily feeding ration. Survival rate and specific growth rate of spawner as well as juvenile produced and number of gravid female checked at the end of each rearing period or every 3 months. After 6 months, average weight of redclaw and huna reaching 146.12 ± 34.47 g and 103.7 ± 29.83 g, respectively. Redclaw produced progeny of 5 size groups and huna produced only 2 groups. Respective to the species, average weight of the first offspring batch was 39.03 ± 5.33 and 26.83 ± 2.09 g. Redclaw at 2 sets of spawner and male grow faster than of 6 sets of spawner and female. No survival rate significant difference among ponds indicates that single–o-shelter technique provides sufficient shelter for spawner to grow and reproduce. Male monosex redclaw culture in earthen pond seems to be more promising than mixed-sex and female monosex culture for consumable size production of either huna or redclaw.